Synthesis, Molecular Characterization, and Antimicrobial Evaluation of Hydrazones Derived from 2-Hydrazinobenzimidazole - Al-Saleem MSM; Mohamed Ahmed MS; Riyadh SM; Alruwaili AH; Zaki MEA; Gomha SM (Drug Design, Development and Therapy, 2025)
Muneera S M Al-Saleem,1 Mohamed S Mohamed Ahmed,2 Sayed M Riyadh,2 Awatif H Alruwaili,3 Magdi E A Zaki,4 Sobhi M Gomha5 1Department of Chemistry, College of Science, Princess Nourah Bint Abdulrahman University, P.O. Box 84428, Riyadh, 11671, Saudi Arabia; 2Department of Chemistry, Faculty of Science, Cairo University, Cairo, Egypt; 3Department of Chemistry, College of Science, Northern Border University, Arar, Saudi Arabia; 4Department of Chemistry, Faculty of Science, Imam Mohammad Ibn Saud Islamic University (IMSIU), Riyadh, Saudi Arabia; 5Department of Chemistry, Faculty of Science, Islamic University of Madinah, Madinah, Saudi ArabiaCorrespondence: Sobhi M Gomha, Email smgomha@iu.edu.sa Magdi E A Zaki, Email mezaki@imamu.edu.saIntroduction: Hydrazones, due to the structural diversity of their nitrogen atoms, possess both electrophilic and nucleophilic properties, enabling strong hydrogen bonding interactions with enzymes and receptors. This study aimed to synthesize novel hydrazone derivatives and evaluate their antimicrobial potential.Methods: Hydrazones were synthesized via condensation of 2-hydrazinobenzimidazole with various aldehydes or ketones using citric acid as an eco-friendly catalyst. The (E)-configuration of the products was confirmed through frontier molecular orbital (FMO) calculations. Antimicrobial activities were assessed against selected Gram-positive and Gram-negative bacteria, and fungi. Molecular docking studies were conducted on the most active compounds ( 3c and 3o) using bacterial and fungal protein targets (2IWC, 2NXW, 1EA1).Results: Compounds 3c and 3o showed strong antimicrobial activity. Docking studies revealed that both compounds interacted with 2IWC via one H-bond donor to THR531 (3.12 Å), mirroring ampicillin. Against 2NXW, they showed dual H-donor bonding to MET404 with binding energies of – 5.96 and – 5.72 kcal/mol, comparable to gentamicin. Both also bound ARG326 in 1EA1 with binding energies of – 5.97 and – 6.0 kcal/mol, similar to nystatin.Discussion: The comparable binding patterns and energies of compounds 3c and 3o to standard antimicrobial agents suggest that they are promising candidates for further development as broad-spectrum antimicrobial agents.Keywords: condensation, HOMO, LUMO, global descriptors, geometrical configuration, pathogenic microorganisms